Consumer perceptions and purchase intention of healthy food products based on promotions and consumer knowledge - Mohammad Haidar Ali; Nurita Andriani; Muhammad Syarif (Institute of Computer Science (IOCS), 2023)
This study aims to compare the effectiveness of framing advertising messages in influencing consumer perceptions which are strengthened by consumer knowledge. It also aims to analyze the effect of advertising on consumer perceptions which are strengthened by consumer knowledge, and its effect on buying interest in healthy food products. This study employed experimental and correlational methods of quantitative approach. The number of respondents in this study amounted to 192 respondents. Collecting research data using observation, interviews, and questionnaires. Data analysis used Independent Sample T-Test, Two Way Anova, Moderated Regression Analysis, and Simple Linear Regression. The results revealed that advertisements with negative message framing are more effective in influencing the perceptions of Trensains High School Students. Negative message framing was more effective for Trensains High School Students with a high level of knowledge about healthy food products, while positive message framing is more effectively used on Trensains High School Students with low knowledge level about healthy food products. Advertising affects the perception of Trensains High School Students on healthy food products. Consumer knowledge strengthens the effect of advertising on the perceptions of Trensains High School Students in healthy food products. Trensains High School Students’ perceptions of healthy food products affect students' purchase intention in healthy food products.